1996
DOI: 10.1097/00007890-199607150-00005
|View full text |Cite
|
Sign up to set email alerts
|

Alloantibody and Intragraft Cellular Response to MHC Class I-Disparate Kidney Allografts in Recipients Tolerized by Donor-Specific Transfusion and Cyclosporine1

Abstract: Congenic PVG.RT1u rats rapidly reject Aa class I-disparate kidney allografts from recombinant PVG R8 donors and we recently demonstrated that anti-class I MHC alloantibody plays a critical role in effecting acute rejection in this experimental model. In this article, we show that PVG.RT1u recipients can be rendered permanently and specifically tolerant to R8 kidney allografts by administration of four weekly donor-specific transfusions (DST) combined with a 7-day course of cyclosporine given with the first DST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…1), and 50% of the R8 heart allografts survived indefinitely. Others showed that pretreating rats with CsA alone had no effect on allograft survival (23). A single injection of R8 blood 2 wk before transplantation and in the absence of CsA had, as expected (2), the opposite effect, inducing accelerated rejection ( Fig.…”
Section: Experimental Modelsupporting
confidence: 51%
See 4 more Smart Citations
“…1), and 50% of the R8 heart allografts survived indefinitely. Others showed that pretreating rats with CsA alone had no effect on allograft survival (23). A single injection of R8 blood 2 wk before transplantation and in the absence of CsA had, as expected (2), the opposite effect, inducing accelerated rejection ( Fig.…”
Section: Experimental Modelsupporting
confidence: 51%
“…Previous studies showed that, in those donor/recipient combinations where primary allograft rejection was mediated by alloantibody, giving recipients a prior blood transfusion sensitized rather than tolerized the recipients (2,15,16,23). As a result, subsequent transplants underwent accelerated destruction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations